(untitled) (Archives of Criminology, 2006)
Patterns of offences committed by youth aged 13–16: in contemporary Poland and fifteen years earlier – in the 1980s. The limit is 1989, a year when major social and political changes in Poland begun. What was different and what was similar in offences between these two groups of youth.